Third‐Party Sociomoral Evaluations in Children With Autism Spectrum Disorder. Issue 5 (8th January 2019) - Li, Tianbi; Decety, Jean; Hu, Xiaoyi; Li, Jiao; Lin, Jinling; Yi, Li
Abstract : We examined explicit and implicit processes in response to third‐party moral transgressions in children with autism spectrum disorder (ASD). Twenty 4‐ to 7‐year‐old children with ASD and 19 typically developing controls evaluated dynamic visual stimuli depicting intentional or accidental harm to persons or damage to objects. Moral evaluations, eye fixations, and pupil dilations toward the stimuli were collected. Results indicate a preserved capacity to understand the mental states of perpetrators and an implicit moral sensitivity to the third‐party harms in children with ASD. Nonetheless, children with ASD showed specific sensitivity and emotional arousal when viewing damage to objects. These findings contribute to the understanding of the underlying mechanisms of moral reasoning in ASD and its possible association with the autistic symptoms.